Bank Wakaf Mikro Sebagai Alternatif Pembiayaan Modal Pelaku UMKM Yang Efektif - Rahib, Muhammad Akbar; Ramadhan, Muhammad Rizky; Fadhillah, Muhammad Fakhri (Diponegoro Journal of Islamic Economics and Business, 2021)
Micro, Small, and Medium Enterprises (MSMEs) are business activities that are able to expand employment opportunity, activate economic activities more broadly, reduce economic inequality and increase income of society, boost economic growth and so on. Besides its large contribution to the national economy, this enterprises face capital adequacy and also human resources as its challange. Therefore, this article proposes Micro Waqf Bank (Bank Wakaf Mikro, BWM) as a alternative financing institution to micro, small and medium enterprises. Using a qualitative approach, hopefully this BWM can enhance standard of living of society and also can reduce inequality and poverty.